2022
DOI: 10.3389/fpsyg.2021.796073
|View full text |Cite
|
Sign up to set email alerts
|

How Parents’ Stereotypical Beliefs Relate to Students’ Motivation and Career Aspirations in Mathematics and Language Arts

Abstract: Despite progress, gender gaps persist in mathematical and language-related fields, and gender stereotypes likely play a role. The current study examines the relations between parents’ gender-related beliefs and their adolescent child’s motivation and career aspirations through a survey of 172 parent-child dyads. Parents reported their gendered beliefs about ability in mathematics and language arts, as well as their prescriptive gender role beliefs. Students reported their expectancies and values in these two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…The math male stereotype exemplifies this issue. Mathematics is represented in social media as a cold, pervasive, more masculine area ( Girelli, 2023 ), whilst other careers, such as pedagogy and language arts, are presented as more feminine ( Chaffee and Plante, 2022 ). As reviewed by Girelli ( 2023 ), the math male stereotype might negatively impact the performance of both genders because it influences the expectation and self-concepts of each individual ability ( Girelli, 2023 ).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The math male stereotype exemplifies this issue. Mathematics is represented in social media as a cold, pervasive, more masculine area ( Girelli, 2023 ), whilst other careers, such as pedagogy and language arts, are presented as more feminine ( Chaffee and Plante, 2022 ). As reviewed by Girelli ( 2023 ), the math male stereotype might negatively impact the performance of both genders because it influences the expectation and self-concepts of each individual ability ( Girelli, 2023 ).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…For example, Palloni (2017) highlights that parents' preferred-gender children get more parental attention, which improves those children's health and nutritional status. Also, Endendijk et al (2015) suggest that in Middle Eastern and North African societies where the gender inequality gap is prominent, parents tend to differentiate between their sons and daughters in preparing them for adult life; such stereotypical behaviors can limit girls' academic and occupational inspiration (Chaffee & Plante, 2020). According to Linberg et al (2008), educated mothers with traditional gender beliefs spend less time with their daughter's math assignments than they do with their sons when compared to egalitarian mothers.…”
Section: Introductionmentioning
confidence: 99%
“…These beliefs can have important implications for students' performance. However, although language stereotypes have been linked to motivation and career intentions (Chaffee, Lou, Noels, & Katz, 2020; Chaffee & Plante, 2022), it is surprising to note that very few studies have linked student‐reported stereotypes with performance in language arts. In a study of English as a foreign language students, stereotype awareness predicted university students' English grades indirectly through self‐efficacy (Kutuk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%